HIGHER EDUCATION LECTURERS’ SUPPORT/ASSISTANCE IN STUDENT LEARNING: STUDY CASE OF LITHUANIAN HIGHER SCHOOLS - Jatkauskienė, Birutė; Nugaras, Modestas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
This article analyses a number of aspects of lecturers’ support/assistance in student learning. Empirical study reveals support/assistance, provided by lecturers, that is focused on: development of interpersonal relationships, informing, facilitation of learning/studies, regulation of relations, modelling of learning/study activities and behaviour, a vision of student learning, student activities. The above listed aspects of support/assistance might serve as a particular performance indicator for some of lecturers in this field, so as to provide a real and effective help and assure a quality of learning and studies.